Teratogenic test of Pandanus conoideus var. yellow fruit extract to development of rat embryo (Rattus norvegicus) - LINTAL MUNA; OKID PARAMA ASTIRIN; SUGIYARTO SUGIYARTO (Nusantara Bioscience, 2010)
Abstract. Muna L, Astirin OP, Sugiyarto. 2010. Teratogenic test of Pandanus conoideus var. yellow fruit extract to development of rat embryo (Rattus norvegicus). Nusantara Bioscience 2: 126-134. This experiment was performed to examine the effect of Pandanus conoideus Lam. var. yellow fruit extract on the percentage of the living fetus, the death intrauterus, heavy and long of fetus, fetus morphology, and skeleton structure of fetus. The experiment was used by 25 pregnant mice that randomly were divided into 5 groups, they contained 5 mice. Each group was given with a different dose. The P1 group (control) was given 1 mL sesame oil, the group P2, P3, P4 and P5 were respectively given the yellow fruit extract 0,02 mL, 0,04 mL, 0,08 mL and 0,16 mL. The P. conoideus var. yellow fruit extract was given orally on day 5 to 17 of gestation (organogenesis period). Observation was carried out on day 18 of gestation by cesarean section to take the fetus from the uterus. Fetus morphology was observed after taking fetus from uterus, whereas observation of skeleton structure was made wholemount preparation with dual colorization, they are Alcian blue and Alizarin Red-S. The result was analyzed with one way ANOVA. Results showed that giving yellow fruit extract didn't influence to the percentage of the living fetus, the death intrauterus, heavy and long of fetus. The effect of giving yellow fruit extract to the maternal was abnormality skeleton (lordosis) of fetus in the dose of 0.16 mL and obstacles to the ossification of fetus.